Differential GPS explained : an exposé of the surprisingly simple principles behind toda´s most advanced positioning technology - Hurn, Jeff (Trimble, 1993)
Foreword - Basic GPS review - What is differential GPS? - Why do we need DGPS? - How does DGPS work? - Who´s using DGPS - What´s next? - Glossary of GPS terms.